Do drug package inserts meet the rules and regulations of Iran's Food and Drug Administration in terms of informing patients? - Tahereh Eteraf-Oskouei; Saeid Abdollahpour; Moslem Najafi; Vahideh Zarea Gavgani (Tabriz University of Medical Sciences, 2019)
Background: Drug package inserts (PIs) are the most accessible source of information for users and are designed to aid the safe use of medicines and avert adverse events. This study measured the conformity of PIs with the health communications standards of Iran's Food and drug Administration (FDA). Methods: This descriptive cross-sectional study evaluated 92 PIs related to 22 best-selling neurological and psychiatric drugs in Iran based on criteria approved by Iran's FDA. Six categories of criteria were considered in evaluating the extent of conformity: I) writing and formatting, II) references, III) drug description, IV) warnings and precautions, V) interactions, and VI) side effects. Each PI was scored based on observation of standards; data was analyzed using Microsoft Excel pivot tables. Results: In total, 2929 items from 92 PIs were evaluated, of which 37 (40.2%) were related to antidepressants, 31 (33.7%) to sedatives and hypnotics, and 24 (26%) to anticonvulsant drugs. The PI content was insufficient in various aspects of conformity with standards in each category. Among the six categories, the best match was found in warnings and precautions with 667items (72.5%), followed by writing and formatting with 663 (69.1%). The lowest conformity was found in the reference category with 194 (26.4%) items. Conclusion: The PIs of Iranian neurological drugs do not fully meet Iran's FDA standards. It is strongly recommended that smart PIs be developed using mobile apps to overcome this problem.